2000
DOI: 10.1515/hf.2000.100
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Labile Terpene Compound in the Assessment of the Age of a Fossil Wood from Siena (Tuscany, Italy)

Abstract: Fossil samples of Pinus sylvestris found near Siena (Tuscany, Italy) in geological formations 2-3 million years old were chemically examined in order to solve the problem of the contrast between the age of geological formations and their good degree of preservation.Comparison with a living Pinus sylvestris was carried out on standard wood component analyses, cation exchange capacity and residual terpene content. The analyses of wood components were close to those of the reference pine, whilst the cation exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…The fossil pine cones even contained several unaltered diterpenoids (bioterpenoids) of the abietane class that were also detected in the extant species (for example, dehydroabietane, dehydroabietol, dehydroabietic acid, and abietic acid), indicating the preservation of characteristic Pinus biomarkers in the Eocene and Oligocene species. Similar diterpenoid patterns with predominant abietane derivatives have been reported previously from archaeological pine resins (for example, Eerkens, 2002) and a Pleistocene Pinus wood (Staccioli et al ., 2000). The terpenoid pattern of the fossil pines showed the closest similarity to the resins of P. bungeana , P. contorta , P. radiata , P. taeda , and P. thunbergii , with a predominance of dehydroabietic acid and smaller amounts of isopimarane‐ and pimarane‐type derivatives.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The fossil pine cones even contained several unaltered diterpenoids (bioterpenoids) of the abietane class that were also detected in the extant species (for example, dehydroabietane, dehydroabietol, dehydroabietic acid, and abietic acid), indicating the preservation of characteristic Pinus biomarkers in the Eocene and Oligocene species. Similar diterpenoid patterns with predominant abietane derivatives have been reported previously from archaeological pine resins (for example, Eerkens, 2002) and a Pleistocene Pinus wood (Staccioli et al ., 2000). The terpenoid pattern of the fossil pines showed the closest similarity to the resins of P. bungeana , P. contorta , P. radiata , P. taeda , and P. thunbergii , with a predominance of dehydroabietic acid and smaller amounts of isopimarane‐ and pimarane‐type derivatives.…”
Section: Discussionsupporting
confidence: 87%
“…Distinct patterns of sesqui‐ and diterpenoids are characteristic of groups of families or even distinct families within the conifers, and can be used as chemosystematic markers (Otto & Wilde, 2001). Chemical analyses of fossil conifer seed cones, leafy shoots, and wood have shown that sesqui‐ and diterpenoids can be preserved in fossil conifers of Tertiary and Late Cretaceous age (Staccioli, Mellerio & Alberti, 1993; Anderson & LePage, 1995; Otto, Kvacek & Goth, 1999; Staccioli et al ., 2000; Tu et al ., 2000; Otto et al ., 2001, 2002b; Otto & Simoneit, 2001, 2002; Otto, White & Simoneit, 2002a; Otto, Simoneit & Rember, 2003). Before and during burial of the conifer remains in sediments, the organic matter is altered through various microbial and physicochemical processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also observed the formation of some other structurally corresponding derivatives, i.e., more stable norabietane and norabietatriene. Later, Staccioli et al detected those abietane-related terpenes in the fossil samples of Scots pine obtained from the 18,000-year-old terrestrial fossil [77]. According to the proposed scheme, the abietane-type terpenes transformation in the fossil samples starts with the disproportionation reaction of abietic acid to form dehydroabietic and tetrahydroabietic acids [78].…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…Therefore, in the present paper, an anatomical and chemical study was attempted in terms of one conifer bogwood piece obtained from the salvaged wood. The chemical analysis of volatile components may also give information on their diagenetic changes, based on previous studies (Simoneit et al 1986 ;Staccioli et al 1993Staccioli et al , 1997Staccioli et al , 1998Staccioli et al , 2000Menchi et al 1995 ;Otto and Simoneit 2002 ;Narita et al , 2007Narita and Kuga 2009 ). For comparison of anatomical and chemical features, several fresh pine samples were collected and analyzed.…”
Section: Introductionmentioning
confidence: 99%